2019
DOI: 10.1021/acs.oprd.9b00133
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of an Atropisomeric Naphthamide by Second-Order Asymmetric Transformation: A Highly Productive Technique

Abstract: Temperature-cycle-induced deracemization (TCID) has been widely studied in the field of chiral separation, ranging from fundamental research to applications. In this study, the secondorder asymmetric transformation (SOAT) of 2-methoxy-1-naphthamide in an azeotropic mixture of ethyl acetate and cyclohexane is compared with TCID, in terms of process productivity. The results indicate that the volumetric productivity using SOAT was over 100times higher than that using TCID, such that a scale-up by a factor of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
0
32
3
Order By: Relevance
“…To confirm the reproducibility of the experiment, we performed SOAT with the same duration and used seed crystals of the opposite enantiomer, which afforded an average ee of 90 % after 20 h. The average volumetric productivity, which indicates the quantity of the desired product that can be obtained per time unit and volume, was 6.5 g h −1 L −1 % for the process. Compared with our previous study, in which we determined the productivity by both SOAT and TCID, the productivity in the present work is low owing to the long crystallization duration caused by the low racemization rate.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…To confirm the reproducibility of the experiment, we performed SOAT with the same duration and used seed crystals of the opposite enantiomer, which afforded an average ee of 90 % after 20 h. The average volumetric productivity, which indicates the quantity of the desired product that can be obtained per time unit and volume, was 6.5 g h −1 L −1 % for the process. Compared with our previous study, in which we determined the productivity by both SOAT and TCID, the productivity in the present work is low owing to the long crystallization duration caused by the low racemization rate.…”
Section: Resultscontrasting
confidence: 75%
“…Viedma ripening (VR) and temperature cycle‐induced deracemization (TCID) are key approaches to deracemization and are being actively studied. We recently reported that second‐order asymmetric transformation (SOAT), a combination of preferential crystallization (PC) and racemization, could achieve relatively high process productivity compared with TCID due to the short processing time. In this study, we used a SOAT‐based approach for an efficient chiral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of obtaining either enantiomer is the same, while the final state of the enantiomer depends on which enantiomer is used in excess . Oketani et al studied the resolution of atropisomeric naphthamide via second-order asymmetric transformation (SOAT) combined with seeding preferential crystallization . The productivity of SOAT is higher than that of temperature-cycle-induced deracemization, and although the former requires enantiomerically pure seed crystals, it could feasibly be part of an efficient process in the future.…”
Section: Seeding Crystallization Instancesmentioning
confidence: 99%
“…In that case, the preferential crystallization receives another name: Second-Order Asymmetric Transformation (SOAT; represented in Figure 12) [61]. This elegant process could be two orders of magnitude more productive than any variant of DIFECS [62]. Supersaturation has to be kept within reasonable limits so that crystal growth and secondary nucleation remain stereoselective.…”
Section: Control Of Macroscopic Chiral Symmetry Breaking By Means Of ...mentioning
confidence: 99%